2016
DOI: 10.2174/1381612822666151125000300
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Process in Alzheimer's and Parkinson's Diseases: Central Role of Cytokines

Abstract: Alzheimer's disease (AD) and Parkinson's disease (PD) are the two most widespread neurological disorders (NDs) characterized by degeneration of cognitive and motor functions due to malfunction and loss of neurons in the central nervous system (CNS). Numerous evidences have established the role of neuroinflammation in the AD and PD pathology. The inflammatory components such as microglia, astrocytes, complement system and cytokines are linked to neuroinflammation in the CNS. More specifically, cytokines have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
106
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(114 citation statements)
references
References 0 publications
3
106
0
3
Order By: Relevance
“…Thus, tissue invasion of blood-derived leukocytes of the adaptive immune system (T and B lymphocytes) is prominent in MS and widely accepted to be disease-promoting 31 . In contrast, the pathogeneses of PD and AD are thought to be naturally occurring processes that involve innate components such as microglia, astrocytes, the complement system, and cytokines 32 . The immunomodulatory properties of SP and its role in autoimmune neuroinflammation have been investigated in more detail using the experimental autoimmune encephalomyelitis (EAE) model, as it resembles MS 33,34 .…”
Section: Neuroinflammation and Substance Pmentioning
confidence: 99%
“…Thus, tissue invasion of blood-derived leukocytes of the adaptive immune system (T and B lymphocytes) is prominent in MS and widely accepted to be disease-promoting 31 . In contrast, the pathogeneses of PD and AD are thought to be naturally occurring processes that involve innate components such as microglia, astrocytes, the complement system, and cytokines 32 . The immunomodulatory properties of SP and its role in autoimmune neuroinflammation have been investigated in more detail using the experimental autoimmune encephalomyelitis (EAE) model, as it resembles MS 33,34 .…”
Section: Neuroinflammation and Substance Pmentioning
confidence: 99%
“…36) The combined treatment of Aβ [31][32][33][34][35] and PGE 2 induced apoptosis in mPGES-1 deficient neurons to the similar level as Aβ 31-35 -treated wild-type neurons. Furthermore, in an in vivo model of AD, genetic disruption of mPGES-1 in Tg2576 mice has been demonstrated to reduce the accumulation of microglia around SPs and attenuated learning impairments determined by the Morris water maze test.…”
Section: Role Of Mpges-1 In Alzheimer's Diseasementioning
confidence: 98%
“…Inflammatory reactions, such as glial activations and production of proinflammatory cytokines around SPs have been demonstrated to accompany the neurodegeneration in AD. 31) Although epidemiological studies have shown that nonsteroidal anti-inflammatory drugs (NSAIDs) which inhibit COX activity can reduce the risk of developing AD, 32) clinical trials of NSAIDs in AD patients have unfortunately not been very fruitful. The protective effects of NSAIDs have been also shown in a transgenic mouse model of AD demonstrating that NSAIDs reduced amyloid deposition and microglial activation.…”
Section: Role Of Mpges-1 In Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Activated microglia and astrocyte clusters at sites of neuritic plaques release a variety of inflammatory mediators 15 , including pro-and anti-inflammatory cytokines that play critical roles in the development and progression of AD 16,17,18,19 . The associations between AD and inflammatory biomarkers, including the interleukins IL-1β, IL-2, IL-4, IL-6, IL-8, IL-12, IL-18, interferon (IFN)-γ, tumor necrosis factor (TNF)-α, transforming growth factor (TGF)-β, and the C-reactive protein have been registered with controversial results 20 .…”
mentioning
confidence: 99%